A Simple and Rapid Puncture Method for Draining Hematoma in Pontine Hemorrhage - Zhang, Mingzhe; Liu, Raynald; Xing, Hongli; Luo, Huixuan; Cui, Leiting; Sun, Zhaosheng (Frontiers in Neurology, 2018)
We present a patient with pontine hemorrhage. On admission, the patient was in a comatose state (Glasgow coma scale, 3). Due to rapid deterioration of his breathing, we immediately performed a direct puncture to the hematoma site. We present a simple and rapid puncture method for drainage of hematomas. The method is described and discussed in detail in this article. The described technique may be beneficial in emergency situations where the condition of the patient, particularly their respiration is declining rapidly.